Odpowiedzi

Najlepsza Odpowiedź!
2009-12-20T17:29:20+01:00
A) 2+ √3/ 4 - √3=
(2+√3)(4+√3) / (4 - √3)(4+√3) = 6 +2√3+4√3+3 / 16 - 3 = 9 + 6√3 / 13

c) 4+ √5 / 2 + √5= (4+√5)(2-√5) / (2+√5)(2-√5) = 8-√5+2√5-5 / 4-5 = 3 + √5 / -1 = -3 -√5
2009-12-20T17:33:47+01:00
Chyba niewymierność, jest to łatwe ^ to potęga
a)2+ √3 2+ √3 4+ √3 2+ √3(4+ √3) 8+4 √3+3+2 √3 11+6 √3
---------= -------- * ----------=----------------= -------------------= -------------
4- √3 4- √3 4+ √3 4^2+ √3^2 16+3 19

reszta na podobnej zasadzie